Identification and carcinogenicity of polycyclic aromatic hydrocarbons in transformer oil. - Pillai, Ilona G. (Cranfield University, 2003)
Insulating oils are rich in polycyclic aromatic hydrocarbons (PAHs) which act as inhibitors of oil breakdown, but are believed to be the main source of oil mutagenicity when converted to their epoxide form by mammalian enzymes. The current industry- recognised measurement of oil risk, the IP 346 method, measures total aromatic content and therefore cannot be directly related to PAH risk. This thesis describes efforts made to establish the contribution of PAH species alone to total oil mutagenicity. Cont/d.